Psychological Well-Being Students in the 2022 Merdeka Student Exchange Program - Tabas Gabe Mulia Siagian; Fellisia Fellisia; Nadya Olivia Pane; Gherry Lineker Sibuea; Achmad Irvan Dwi Putra; Rina Mirza (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research focuses on the psychological well-being of students from Prima Indonesia University who participated in the 2022 PMM Program. With the academic and social challenges faced by students, this study aims to understand their impact on students' psychological well-being. To achieve this goal, this study uses Ryff's theoretical framework to assess six dimensions of psychological well-being. In applying the research methodology, a qualitative approach is used. Informants were selected through purposive sampling, with characteristics as students of the 2022 PMM Program who are currently in their fifth semester. Data was collected through observation and structured interviews. The results of the study show that UNPRI students who participated in the 2022 Merdeka Student Exchange Program have a good level of psychological well-being, with dimensions of autonomy, positive relationships, mastery of the environment, personal growth, meaningful life goals, and self-acceptance identified as key factors impacting their psychological well-being.Penelitian ini berfokus pada kesejahteraan psikologis mahasiswa Universitas Prima Indonesia yang berpartisipasi dalam Program PMM 2022. Dengan tantangan akademis dan sosial yang dihadapi oleh mahasiswa, penelitian ini bertujuan untuk memahami dampaknya terhadap kesejahteraan psikologis mahasiswa. Untuk mencapai tujuan ini, penelitian ini menggunakan kerangka teori Ryff untuk menilai enam dimensi kesejahteraan psikologis. Dalam menerapkan metodologi penelitian, digunakanlah pendekatan kualitatif. Informan dipilih melalui metode purposive sampling, dengan karakteristik sebagai mahasiswa Program PMM 2022 yang saat ini sedang menempuh semester lima. Data dikumpulkan melalui observasi dan wawancara terstruktur. Hasil penelitian menunjukkan bahwa mahasiswa/i UNPRI yang mengikuti Program Pertukaran Mahasiswa Merdeka Tahun 2022 memiliki tingkat kesejahteraan psikologis yang baik, dengan dimensi otonomi, hubungan positif, penguasaan lingkungan, pertumbuhan pribadi, tujuan hidup yang bermakna, dan penerimaan diri teridentifikasi sebagai faktor kunci yang berdampak pada kesejahteraan psikologis mereka.